Comparative Study on Refusal Strategy between American English Native Speakers and Indonesian EFL Learners - Sartika Sartika; Endang Fauziati; Sri Marmanto; Iwan Jazadi (VELES Voices of English Language Education Society, 2020)
This article analyses refusal strategies applied by American speakers of English and Indonesian students of English as a foreign language. This study is descriptive qualitative research. Twenty participants contributed in this study. Furthermore, the data were gathered from Discourse Completion Test and interview. In order to get trustworthiness of the data, source of triangulation, member checking and external audit were applied. Then, Miles and Huberman’s flowchart was used to analyze the data. The result show that: (1) both of the groups use fourteen refusal strategies namely direct no, inability, avoidance, hedging, excuse, wish, statement of alternative, promise of future acceptance, statement of regret, acceptance that function as refusal, set condition for past acceptance, gratitude/appreciation, pause fillers and statement of positive feeling/opinion; (2) some similarities and differences of strategies were found being used by both groups. Eleven strategies were found to be similar, namely, direct no, inability, postponement, excuse, statement of alternative, statement of regret, wish, lack of enthusiasm, gratitude/appreciation, pause fillers and statement of positive feeling. Meanwhile, the different refusal strategies used by those groups were hedging, promise of future acceptance and set condition for past acceptance.